PENGARUH PENGETAHUAN KOPERASI, MOTIVASI BERKOPERASI DAN PELAYANAN KOPERASI TERHADAP MINAT MENJADI ANGGOTA KOPERASI MAHASISWA - Yohana Jaya; Rusno Rusno; Auliana Farrabanie Al Arsy (Jurnal Riset Pendidikan Ekonomi, 2019)
This study uses a population of 335 students of Universitas Kanjuruhan Malang who entered the cooperative in 2017-2018 and then the sampling technique was taken 25% of the population using proportional random sampling. The results of this study indicate that: 1) cooperative knowledge, cooperative motivation, cooperative services have a joint effect on the interests of students becoming members of student cooperatives in Universitas Kanjuruhan Malang, 2) cooperative knowledge has a positive and significant effect on the interests of students becoming members of student cooperatives, 3 ) motivation to operate positively and significantly influence the interests of students to become members of student cooperatives, 4) cooperative services have a positive and significant effect on the interests of students to become members of student cooperatives.